Prognostic value of the Residual Cancer Burden index according to breast cancer subtype: Validation on a cohort of BC patients treated by neoadjuvant chemotherapy - Hamy, Anne-Sophie (PLoS One, 2020)
INTRODUCTION: The Residual Cancer Burden (RCB) quantifies residual disease after neoadjuvant chemotherapy (NAC). Its predictive value has not been validated on large cohorts with long-term follow up. The objective of this work is to independently evaluate the prognostic value of the RCB index depending on BC subtypes (Luminal, HER2-positive and triple negative (TNBCs)). METHODS: We retrospectively evaluated the RCB index on surgical specimens from a cohort of T1-T3NxM0 BC patients treated with NAC between 2002 and 2012. We analyzed the association between RCB index and relapse-free survival (RFS), overall survival (OS) among the global population, after stratification by BC subtypes. RESULTS: 717 patients were included (luminal BC (n = 222, 31%), TNBC (n = 319, 44.5%), HER2-positive (n = 176, 24.5%)). After a median follow-up of 99.9 months, RCB index was significantly associated with RFS. The RCB-0 patients displayed similar prognosis when compared to the RCB-I group, while patients from the RCB-II and RCB-III classes were at increased risk of relapse (RCB-II versus RCB-0: HR = 3.25 CI [2.1–5.1] p<0.001; RCB-III versus RCB-0: HR = 5.6 CI [3.5–8.9] p<0.001). The prognostic impact of RCB index was significant for TNBC and HER2-positive cancers; but not for luminal cancers (P(interaction) = 0.07). The prognosis of RCB-III patients was poor (8-years RFS: 52.7%, 95% CI [44.8–62.0]) particularly in the TNBC subgroup, where the median RFS was 12.7 months. CONCLUSION: RCB index is a reliable prognostic score. RCB accurately identifies patients at a high risk of recurrence (RCB-III) with TNBC or HER2-positive BC who must be offered second-line adjuvant therapies.